Association of the origin of contamination and species of microorganisms with short‐term survival in dogs with septic peritonitis. Issue 3 (24th November 2022) - Uetsu, Y; Houston, D; Bailey, C; Kilpatrick, S
Abstract : Objective: To assess the association between anatomical location of contamination and mortality in dogs with gastrointestinal and biliary origin of septic peritonitis. Methods: Medical records at two private referral hospitals between 2003 and 2020 were retrospectively reviewed. Cases were included if the origin of contamination was confirmed intraoperatively within the gastrointestinal or biliary tract. Cases were excluded if the dog died or was euthanized intraoperatively or where the data regarding the origin of contamination were not available. The association of anatomical origin with survival was assessed specifying the locations as stomach, small intestine, large intestine and biliary tract. The gastrointestinal tract origin was further subdivided into pylorus, nonpylorus, duodenum, jejunum, ileum, caecum and colon. Results: The overall survival rate was 75.9% (n = 44/58). There were no significant differences in survival among different anatomical origins of contaminations before or after subdivision ( P  = 0.349 and 0.832, respectively). Also, there was no association between isolated microorganism species in microbiological culture and the anatomical origin ( P  = 0.951) and the microorganism species was not associated with survival ( P  = 0.674). Conclusions: There was no association between anatomical location of leakage, microorganism species and survival although further studies are warranted to analyse the relationships between anatomical leakage site and microorganism species as well as microorganism species and mortality.